2015
DOI: 10.3389/fnhum.2015.00057
|View full text |Cite
|
Sign up to set email alerts
|

Contagious itch: what we know and what we would like to know

Abstract: All humans experience itch in the course of their life. Even a discussion on the topic of itch or seeing people scratch can evoke the desire to scratch. These events are coined “contagious itch” and are very common. We and others have shown that videos showing people scratching and pictures of affected skin or insects can induce itch in healthy persons and chronic itch patients. In our studies, patients with atopic dermatitis (AD) were more susceptible to visual itch cues than healthy. Also, personality traits… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

5
81
0
4

Year Published

2015
2015
2019
2019

Publication Types

Select...
5
3

Relationship

1
7

Authors

Journals

citations
Cited by 80 publications
(90 citation statements)
references
References 51 publications
5
81
0
4
Order By: Relevance
“…Aprepitant may be considered in recalcitrant cases of CP. Both in individuals with healthy skin and patients with CP, pruritus and scratching can be elicited by mental and visual stimuli and by observing other people [ 39,40 ] . It has been shown that, compared to individuals with healthy skin, patients with AD react to the same stimuli with more pronounced pruritus and scratching [ 41 ] .…”
Section: Recommendationmentioning
confidence: 99%
“…Aprepitant may be considered in recalcitrant cases of CP. Both in individuals with healthy skin and patients with CP, pruritus and scratching can be elicited by mental and visual stimuli and by observing other people [ 39,40 ] . It has been shown that, compared to individuals with healthy skin, patients with AD react to the same stimuli with more pronounced pruritus and scratching [ 41 ] .…”
Section: Recommendationmentioning
confidence: 99%
“…Papoiu et al, 2011;Schut et al, 2015a). Similar to pain, itch is a somatosensory sensation that can be a considerable burden for patients, especially when symptoms are chronic.…”
Section: Introductionmentioning
confidence: 99%
“…[104][105][106] Despite lacking clear evidence, [107] , it is speculated that in patients with delusional infestation, overactive contagious itch centres or an overactivity of the mirror neuron system may play a role. [98,108] Contagious itch points to the suggestibility of itch and potentially substantial placebo effects. [95] It has even been speculated that if there is a central source able to produce itch, there must also be a way to reverse the mechanism and produce cure.…”
Section: Contagious Itch Placebo Effects and Nocebo Effects On Itchmentioning
confidence: 99%
“…[68] Interestingly, several brain regions linked to contagious itch are implicated in the simulation of actions, the so-called mirror neuron system, including the premotor cortex (BA6) and adjacent BA44. [97][98][99][100] This system is believed to be implicated in other archaic social contagious "resonance reactions" such as yawning (linked to BA 6 activity [101] ), laughing and the development of empathy. [102,103] Patients with autism, schizophrenia and psychopathy seem to have a mirror neuron system deficiency as measurable by an impaired ability of contagious yawning.…”
Section: Contagious Itch Placebo Effects and Nocebo Effects On Itchmentioning
confidence: 99%